RATIONALITY OF PUBLIC MANAGEMENT: A look at exceptional measures in a crisis environment in Portugal facing COVID-19 - Catarino, João Ricardo; Lopes, Miguel Pereira; Gonçalves, Sónia Pedroso; de Moraes e Soares, Ricardo (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2021)
The COVID-19 pandemic represents an unprecedented challenge for governments around the world. Despite the differences recorded in virus evolution and in the number of victims involved, it is consensual that Society is experiencing changes with consequences that are still unpredictable. Government responses have varied in terms of timing and content, which makes the sharing and reflection urgent. This article focuses on the Portuguese Public Administration’s response, mainly on the areas of leadership, human resources management and education, aiming to identify a set of the most significant public measures taken within the management of COVID-19. The analysis of the exceptional measures allowed to conclude that the Portuguese public administration adopted management practices close to the market mechanisms, adopting private management tools, marked by flexibility, autonomy, decentralization. Another characteristic that stands out is the co-leadership between political and administrative authorities, i.e., a broader public management concerned with the sustainability of collective life.